TEACHINGENGLISH VOCABULARY TO NON-LINGUISTIC SPECIALTY STUDENTS - Temirbekova, Zh.A. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
This article is devoted to the main problems connected with teaching foreign vocabulary to students of non-linguistic specialties, as well as a methodological model and examples of exercises in order to increase the effectiveness of teaching English vocabulary to students of non-linguistic specialties.
Keywords: foreign vocabulary; nonlinguistic specialty; methodological model; methods of teaching EL